Assessment of Happiness Levels Through Health Screening Among Second-Semester Students of the Nursing Science Program: Skrining Kesehatan Tingkat Kebahagiaan pada Mahasiswa Semester II Program Studi Ilmu Keperawatan - Rosyad, Yafi Sabila; Khoeriyah, Salis Miftahul; Subantara, Dandi Oka (Sahabat Publikasi Kuu, 2025)
Introduction: Nursing students generally experience a high academic burden due to the need to meet rigorous academic expectations, intense competition, and a high level of responsibility. These factors can significantly impact their mental health, including overall happiness and well-being. Methods: This community service initiative targeted 78 second-semester students from the Nursing Science Program. A quantitative analysis was conducted through health screening using the Oxford Happiness Questionnaire (OHQ) to measure their happiness levels. Results: The health screening revealed that 67.95% of the students were categorized as